ANALISIS PENENTUAN HARGA POKOK PRODUKSI PADA INDUSTRI TAHU TEMPE DI PEMATANGSIANTAR - Elfina Okto Damanik (Sekolah Tinggi Ilmu Ekonomi Surya Nusantara, 2020)
This study aims to analyze the cost of production in the home industry of tahu tempe Mr. Joko, Jalan Melati, Pematangsiantar City. The cost of production is calculated based on the costs incurred in the purchase of direct raw materials, direct labor and factory overhead costs. The costof production so far has not been calculated properly, so the selling price of the product is only based on estimates. During the last 6 months, there was a significant change in prices of the main raw materials for soybeans.. The price increase was due to the accuracy of the fasting month and Eid al-Fitr. Tahu tempe production processes use 2 workers. In tempe and tahu products, home industry Mr Joko packs them using leaf packaging. The production of tahu and tempe produced by Mr. Joko's home industry is capable of producing tempe up to 2000kg and tahu up to 1800kg every month. Based on the results of research conducted on costs - costs incurred from the purchase of raw materials to production ready to sell (already in packaging), the difference in the cost of production of tempe produced by researchers counts with the result of the owner count for 6 months amounting to Rp 1.770.410 and tahu equal to Rp 1.727.654. Some important aspects in determining production costs are not taken into account by the owner such as depreciation costs, maintenance costs, and overhead costs. The calculation of the cost of production of the home industry of tahu tempe Mr Joko is not quite right. Keywords: Cost of Production